2021
DOI: 10.3390/life11040320
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA NEAT1 as a Potential Candidate Biomarker for Prostate Cancer

Abstract: Background: Prostate cancer (PCa) remains one of the leading causes of cancer-related mortality in men worldwide, mainly due to unsatisfactory diagnostic methods used at present, which lead to overdiagnosis, unnecessary biopsies and treatment, or misdiagnosis in early asymptomatic stages. New diagnostic biomarkers are needed for a correct and early diagnosis. Long noncoding RNAs (lncRNAs) have been broadly studied for their involvement in PCa biology, as well as for their potential role as diagnostic biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…NEAT1 knockdown enhanced the sensitivity of cells to PTX through the miR-194/ZEB1 axis [216]. The potential of NEAT1 as a possible diagnostic marker has been proposed in several cancers, such as prostate [217] and breast [218]. For EOC, a serum biomarker panel that combines gene and protein expression was proposed as a method for early detection of EOC, and NEAT1 is one of the proposed lncRNA in this panel [219].…”
Section: Neat1mentioning
confidence: 99%
“…NEAT1 knockdown enhanced the sensitivity of cells to PTX through the miR-194/ZEB1 axis [216]. The potential of NEAT1 as a possible diagnostic marker has been proposed in several cancers, such as prostate [217] and breast [218]. For EOC, a serum biomarker panel that combines gene and protein expression was proposed as a method for early detection of EOC, and NEAT1 is one of the proposed lncRNA in this panel [219].…”
Section: Neat1mentioning
confidence: 99%
“…There are two subtypes of lncRNA NEAT1, namely, NEAT1_1 (3.7 kb) and NEAT1_2 (23 kb) [ 21 ]. Nitusca et al reported that NEAT1 could serve as a diagnostic biomarker for prostate cancer [ 22 ]. LncRNA NEAT1 is also essential in immune regulation [ 23 ].…”
Section: Introductionmentioning
confidence: 99%